2022
DOI: 10.1007/s00228-022-03276-4
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence among persons with coronary heart disease and associations with blood pressure and low-density-lipoprotein-cholesterol

Abstract: Purpose To describe medication adherence to lipid-lowering drugs (LLDs), antihypertensive drugs, and acetylsalicylic acid (ASA) among persons with coronary heart disease (CHD) and explore its association with low-density-lipoprotein (LDL)-cholesterol, and systolic and diastolic blood pressure. Methods Based on record linkage between the seventh wave of the Tromsø Study and the Norwegian Prescription Database, medication adherence was calculated as the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…Data analysis was carried out using the path analysis method that made it possible to more accurately investigate the interactions between multiple factors and thus determine the direct, indirect, and total effects of demographic, clinical, and behavioral variables on medication adherence. Results showed that more than half of the participants (61.8%) adhered to their medication regimen, which is consistent with previous studies (He et al, 2022; Pedersen et al, 2022; Silva Tinoco et al, 2021). It was also shown that greater illness perception, better self-efficacy, and higher education had a positive effect on medication adherence, and increasing age also had a negative effect on it.…”
Section: Discussionsupporting
confidence: 91%
“…Data analysis was carried out using the path analysis method that made it possible to more accurately investigate the interactions between multiple factors and thus determine the direct, indirect, and total effects of demographic, clinical, and behavioral variables on medication adherence. Results showed that more than half of the participants (61.8%) adhered to their medication regimen, which is consistent with previous studies (He et al, 2022; Pedersen et al, 2022; Silva Tinoco et al, 2021). It was also shown that greater illness perception, better self-efficacy, and higher education had a positive effect on medication adherence, and increasing age also had a negative effect on it.…”
Section: Discussionsupporting
confidence: 91%
“…Several other studies have investigated patterns of statin use in the realworld setting. 28,[34][35][36][37] In line with our results, previous studies indicate that there is an underutilization of high-intensity statin therapy 35,36 and that patients at high risk for CV events have high rates of discontinuation and poor adherence. 31,36 While many studies of adherence to lipid lowering treatment have focused on individual patients and specific lipid lowering drugs, we explore all three drug groups with a public health approach.…”
Section: Findings In Other Studiessupporting
confidence: 89%
“…Even though we in this study do not have information on LDL-cholesterol levels, other Norwegian studies find clear association between lipid lowering treatment, LDL-cholesterol levels and CVD risk. 6,28,29 In line with this, a large European study shows that a significant number of patients do not achieve the guideline-recommended treatment targets for LDL-cholesterol in daily clinical practice and that few are using combination with non-statin lipid lowering drugs. 30 Immediate, combination therapy with statins and ezetimibe, at least to high-risk patients, has therefore recently been recommended by a European Position document.…”
Section: Discussion Of Own Findingsmentioning
confidence: 83%